2011
DOI: 10.1002/anie.201002307
|View full text |Cite
|
Sign up to set email alerts
|

J‐Aggregates: From Serendipitous Discovery to Supramolecular Engineering of Functional Dye Materials

Abstract: J-aggregates are of significant interest for organic materials conceived by supramolecular approaches. Their discovery in the 1930s represents one of the most important milestones in dye chemistry as well as the germination of supramolecular chemistry. The intriguing optical properties of J-aggregates (in particular, very narrow red-shifted absorption bands with respect to those of the monomer and their ability to delocalize and migrate excitons) as well as their prospect for applications have motivated scient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

70
1,886
1
27

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 2,213 publications
(2,037 citation statements)
references
References 322 publications
70
1,886
1
27
Order By: Relevance
“…(iii) The overlap between aromatic rings may occur in a plane-to-plane (H-type) or an edge-to-edge (J-type) orientation, driving the self-assembly process toward a specic geometry. 4 Aromatic/aromatic interactions have been shown to induce the self-assembly of pentapeptide derivatives in water to form nanobers and supramolecular hydrogels. 5 More strikingly, also the Phe-Phe dipeptide, an important structural motif of the Ab peptide, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…(iii) The overlap between aromatic rings may occur in a plane-to-plane (H-type) or an edge-to-edge (J-type) orientation, driving the self-assembly process toward a specic geometry. 4 Aromatic/aromatic interactions have been shown to induce the self-assembly of pentapeptide derivatives in water to form nanobers and supramolecular hydrogels. 5 More strikingly, also the Phe-Phe dipeptide, an important structural motif of the Ab peptide, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…J-aggregates, [82][83][84] named after Jelley, are relatively ordered molecular arrays whose transition dipoles are arranged in such a way that large exciton delocalization is present in the low-energy excitation bands. They have technologically relevant optical properties such as a narrow absorption band that exhibits a large absorption intensity at the expense of a large number of quasi-dark excited states.…”
Section: B Stokes Shifts In Ideal J-aggregatesmentioning
confidence: 99%
“…1,2 Due to these remarkable properties, PDIs are materials that, in additon to their use as industrial important pigments, 3 have been utilized or explored in other various optical and electronic applications, 4,5,6,7,8 or for liquid crystals, 9 and for highly fluorescent J-aggregates. 10 Also, the incorporation of metal centers to PDI structures at the imide region or at bay positions offers the possibility to modify the photochemistry and photophysics, and as a result their potential applications. 11 We have published platinum organometallic complexes of perylene and perylene monoimide (N-(2,5-di-tertbutylphenyl)perylene-3,4-dicarboximide, PMI) with Pt σ-bonded directly to the perylene core, 12 and have found that, in spite of the fact that attaching directly metal centers to aromatic cores of organic chromopheres is usually very detrimental, the coordination of Pt has only a moderate quenching effect on the fluorescence (our organoplatinum derivatives kept 70-80% of the fluorescence intensity of the mother organic molecule).…”
Section: Introductionmentioning
confidence: 99%